2019
DOI: 10.1186/s13007-019-0532-7
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for image-based large-flowered chrysanthemum cultivar recognition

Abstract: BackgroundCultivar recognition is a basic work in flower production, research, and commercial application. Chinese large-flowered chrysanthemum (Chrysanthemum × morifolium Ramat.) is miraculous because of its high ornamental value and rich cultural deposits. However, the complicated capitulum structure, various floret types and numerous cultivars hinder chrysanthemum cultivar recognition. Here, we explore how deep learning method can be applied to chrysanthemum cultivar recognition.ResultsWe propose deep learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…Flowers with ornamental phenotype have brought a pleasing visual feast to humans due to their unique shapes, rich colors, and varied textures, which is important for flower phenotype research through computer vision. Recent studies have applied deep learning-based methods to flower recognition and made a series of important progress [ 9 – 14 ]. In particular, Lee [ 9 ] studied Convolutional Neural Networks (CNN) to learn unsupervised feature representations for 44 different plant species.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Flowers with ornamental phenotype have brought a pleasing visual feast to humans due to their unique shapes, rich colors, and varied textures, which is important for flower phenotype research through computer vision. Recent studies have applied deep learning-based methods to flower recognition and made a series of important progress [ 9 – 14 ]. In particular, Lee [ 9 ] studied Convolutional Neural Networks (CNN) to learn unsupervised feature representations for 44 different plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Deep Convolutional Neural Networks (DCNN) based hybrid method is applied to flower species classification on Flower17 and Flower102 datasets in [ 13 ]. Liu [ 14 ] proposed a method of large-flowered chrysanthemum cultivar recognition. In the context of deep learning [ 15 ], at least thousands of training samples are required for each class to saturate the performance of DCNN on known classes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very effective for real-life object detection, recognition and classification [7] . In the field of agricultural research, deep learning technology in agriculture includes crop/weed recognition, fruit harvesting [8] , and plant recognition [9] . Similarly, recent studies have also focused on the identification of plant diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it has been shown that even in field environments, the images collected by typical smart phones or digital cameras can be used to train deep CNN by transfer learning for an accurate wine grape species recognition.Specifically, in this study, the accuracy of our trained model can reach 99.91%, and the early dataset augmentation plays an important role in achieving the performance. In the case of using transfer learning to solve the problem of object recognition, in order to improve the accuracy of the detection model, images are often acquired in a controlled environment in the laboratory[19]. The image preprocessing method is used to enhance the object or weaken the background on the other hand.…”
mentioning
confidence: 99%